Estudo do sistema vítreo oxifluorofostato PKAL (P2O5-KF-AL2O3): dopagem com TM2O3, CRO3 e desenvolvimento de compósitos phosphor-in-glass - SILVA NETO, Otávio Cândido da (2024)
This work aimed to synthesize and characterize a new vitreous system, obtained by the melt-quenching method. The samples produced in the P2O5-KF-Al2O3 (PKAl) system are part of the family of glasses that combine properties of oxides and fluorides, called oxyfluorides. A series of glass matrices were synthesized, varying the concentration of Al2O3 from 8 to 20 mol%, were explored in different ways. Studies were carried out on the glasses based on doping with the compounds Tm2O3 and CrO3, varying the concentration of these dopants (from 0.25 to 1.00 mol%), in addition, a study was carried out on PKAl glass as precursor glass matrix of the composite called phosphor-in-glass (PiG), combining the properties of PKAl glass with luminescent properties of the yttrium aluminum garnet (YAG) material doped with Dy3+, Sm3+, Tb3+ , and Eu3+ ions, also prepared in this work. The structural, vibrational, thermal, optical and luminescent properties were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), UV-VIS-NIR optical absorption spectroscopy, photoluminescence measurements, index refraction, volumetric density, differential scanning calorimetry (DSC), among others. Some additional parameters, such as Tanabe-Sugano diagram, optical band gap and chromaticity diagram (CIE) were also calculated in the studies. Finally, the results obtained suggest that the synthesized glasses are promising candidates for use in the development of photonic optical devices, such as light filters, wLEDs, LEDs and NIR-LEDs, as well as solid-state lasers.